Comparative Study of Al-Azhar & Al-Mishbah's Interpretation of the Qur'an, Surah Al-Baqarah Verse 153 Regarding the Concept of Patience - Karlina, Yulis; Rhain, Ainur (Universitas Muhammadiyah Surakarta, 2023)
This research entitled: